COVID-19 Lockdown Time Capsule of South Africa, April 2020 - Various Authors (The Thinker)
South Af rica had one of the strictest Covid lockdowns in the world starting on the 26th of March and lasting for 35 days. With five weeks of quarantine where only essential services were open, all educational institutions, places of worship and workplaces were shut down and people had to shelter in place. Walking on the streets was even prohibited except to buy food. The country was slowly moved through varying restrictions over the next 5 months as the health risks decreased as the virus was slowed down effectively.